Evaluation of Postoperative Radiotherapy Effect on Survival of Resected Stage III-N2 Non-small Cell Lung Cancer Patients - Gao, Fei; Li, Nan; Xu, YongMei; Yang, GuoWang (Frontiers in Oncology, 2020)
Objective: The role of postoperative radiotherapy (PORT) in resected stage IIIA-N2 non-small cell lung cancer (NSCLC) patients remains controversial. This study aimed to explore the effect of PORT on survival of resected stage IIIA-N2 NSCLC patients. Methods: Resected stage IIIA-N2 NSCLC patients aged 18 years or older were identified from the SEER (Surveillance, Epidemiology, and End Results) database from 2010 to 2015. Cox regression analysis was used to identify factors including PORT associated with survival time. A subgroup analysis of patients stratified by number of lymph node metastases was also performed. Overall survival (OS) and overall mortality were compared among the different groups. Results: A total of 3,445 patients were included in the study. Multivariate Cox analysis showed that PORT had no significant impact on survival of patients with <6 positive lymph node [hazard ratio (HR) = 1.012, P = 0.858, 95% CI: 0.886–1.156]. Postoperative chemotherapy (POCT) (HR = 0.605, P < 0.001, 95% CI: 0.468–0.783) and PORT (HR = 0.724, P = 0.007, 95% CI: 0.574–0.914) are both favorable prognostic factors for stage IIIA-N2 patients with ≥6 positive lymph nodes. In 2,735 patients who featured <6 number of positive regional lymph nodes, patients who received PORT had better survival and lower 3-years and 5-years overall mortality rate than patients who underwent surgery only (41 vs. 28 months, P < 0.015). There was no significant difference in the survival of postoperative patients who underwent POCT in view of whether received PORT (44 vs. 53 months, P = 0.176). A total of 710 patients who featured ≥6 number of positive regional lymph node metastasis were divided into two groups by PORT. PORT did not prolong survival for postoperative patients who did not receive chemotherapy (12 vs. 15 months, P = 0.632). PORT showed a significant advantage in influencing OS in patients who received PORT combined with POCT as compared with those who received POCT only (32 vs. 25 months, P = 0.006). Conclusions: For IIIA-N2 patients with <6 lymph node metastases, use of PORT can be encouraged to improve survival. For patients with ≥6 positive lymph nodes, PORT combined with POCT significantly improved OS and decreased overall mortality.